Pengaruh Game Online Terhadap Prestasi Siswa SMP Muhamadiyah Kelas IX Kota Ambon - Fuad Anwar Maruni; Dwi Partini (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
The development of digital technology has brought various changes to everyday life, including in the field of education. One prominent phenomenon is the increasing use of online games by students, which can have both positive and negative impacts on their behavior and academic performance. This study aims to analyze the extent to which online games affect the academic achievement of students at SMP Muhammadiyah Ambon. The research uses a mixed-method approach, combining qualitative and quantitative methods, with data collected through questionnaires and interviews, and analyzed using multiple linear regression. The results show that the impact of online games varies depending on the students' ability to manage their time. Some students who are able to limit their gaming time and prioritize studying continue to show good academic performance. However, students who struggle to control the amount of time spent on gaming tend to experience a decline in academic achievement. This indicates that the influence of online games is not entirely negative if balanced with good self-control. Therefore, it is important for students, parents, and teachers to work together to raise awareness of the importance of time management and self-regulation, so that gaming activities do not interfere with, but rather support, optimal learning outcomes.